The Effect Of Instagram Social Media Use On The Political Literacy Of Generation Z Of Fisip UMC Students In The 2024 Election - Mita Septiyani; Sastra Abijaya (ann4publisher@gmail.com, 2026)
Background. Instagram, in its development, is not only a means of entertainment but has also become a source an information in the political field. In the context of the 2024 election, Instagram is one of the strategic platforms Generation Z uses as a medium for political literacy. Aims. This study aims to determine the influence of Instagram use on the political literacy of FISIP UMC Generation Z students during the 2024 Election. FISIP UMC students are part of Generation Z, an active group on Instagram. As part of Generation Z, they are actively exposed to social media in their daily lives. Therefore, it is interesting to examine whether Instagram use influences the political literacy of FISIP UMC Generation Z students during the 2024 election. Methods. This study uses a quantitative research method with an associative approach, which is an approach that measures the extent to which independent variables affect dependent variables. The sampling technique used is Stratified Random Sampling with a total of 67 respondents from FISIP UMC students of the 2022 batch. The data collection technique uses a questionnaire via Google Forms with Likert-scale measurements. Then the data processing technique uses simple linear regression. The theoretical basis applied in this study is social media theory and political literacy theory. Result. Based on the results of the study, it is known that there is an influence of Instagram social media use on the political literacy of Generation Z. A regression coefficient value of 0.634 was obtained, which was positive, so the effect of social media use has a positive effect on political literacy. and the value of the table > t-table (11.383 > 1.6686). Conclusion. The results of the statistical test also showed that the determination coefficient (R Square) of 0.666 indicated that 66.6% of the variation in political literacy was influenced by the use of Instagram. The remaining 33.4% is influenced by other variables not studied in this study.